1997
DOI: 10.1046/j.1365-2141.1997.4463256.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activity of high‐dose factor VIIa is independent of tissue factor

Abstract: High‐dose recombinant factor VIIa has been successfully used as therapy for haemophiliacs with inhibitors. The mechanism by which high‐dose factor VIIa supports haemostasis is the subject of some controversy. Postulating a mechanism in which activity is dependent on tissue factor at the site of injury explains the localization of activity but not the requirement for high doses. Postulating a mechanism in which factor VIIa acts on available lipid independently of tissue factor explains the requirement for high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
389
1
8

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(414 citation statements)
references
References 21 publications
16
389
1
8
Order By: Relevance
“…To our knowledge, there have not been previous reports of FVIIa inside platelets. In 1997, Monroe and colleagues 41,42 reported that rFVIIa could weakly bind to the membrane of activated platelets, where it could promote thrombin generation, but no reference was made to a possible presence of FVIIa inside platelets. Under physiological conditions, levels of FVIIa in plasma are very low (approximately 1% of the total circulating FVII).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have not been previous reports of FVIIa inside platelets. In 1997, Monroe and colleagues 41,42 reported that rFVIIa could weakly bind to the membrane of activated platelets, where it could promote thrombin generation, but no reference was made to a possible presence of FVIIa inside platelets. Under physiological conditions, levels of FVIIa in plasma are very low (approximately 1% of the total circulating FVII).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that high concentrations of FVIIa induce platelet activation, generate platelet surface factor IXa and Xa which lead to thrombin generation on the platelet surface, and also to the formation of hemostatic plaque despite low platelet numbers [22,34]. Moreover, very high concentrations of rFVIIa may also result in a saturation of all available tissue factor exposed at the site of injury, as well as in extravascular spaces, leading to local thrombin generation and thrombus formation [38].…”
Section: How Rfviia May Improve Hemostasis In Itpmentioning
confidence: 99%
“…Because of the dilution of blood proteins, including factor VII, in our reaction system, one might have expected to see significant platelet activation at lower concentrations of rFVIIa. An alternative or perhaps complementary explanation may be that, as rFVIIa is reported to have a lower affinity for activated platelet surfaces than for TF, relatively high rFVIIa concentrations are required (Monroe et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that high-dose rFVIIa can activate factors IX and X on the surface of platelets by a mechanism independent of TF (Monroe et al, 1997Hoffman et al, 1998). These observations may help to explain the efficacy of rFVIIa in the treatment of haemophilia A and B.…”
mentioning
confidence: 99%
See 1 more Smart Citation